Social Media for Sustainable Development: Challenging Participatory Development Practices to Re-learn and Realign Stakeholder Practices in Tamale Metropolis, Ghana - Mohammed, Ismail; Fiadzawoo, Jonas Kwabla (European Scientific Journal, ESJ, 2023)
This study aims at finding out how social media has been explored for the enhancement of sustainable development in the Tamale Metropolis. It was based on Uses and Gratification Theory (Katz, Blumler, & Gurevitch,1974). It adopted a mixed approach and relied on questionnaires and interview guides for collecting data. Local community leaders (N. 25) were interviewed. A hundred questionnaires were also administered with Google Forms. The interview data were analysed qualitatively and the results were presented based on content and themes. The data obtained through the questionnaires were processed and presented descriptively in percentages. Findings showed that social media was highly used among the participants (92%). Those within higher education were 44% while those without higher education numbered 57%. It was found that there was males dominance in local community development support groups. Sixty-one percent of the participants used social media to support sustainable community development. They employed the media to foster citizensâ€™ participation and contribution to sustainable development. The study, therefore, proposed to community groups to have their social media groups registered with the authorities to promote their visibility. The study also called for proper evaluation of citizens’ media activities in order to support their contribution to sustainable development, which it argued will strengthen efforts to achieve SDGs 11 and 17.